Empowering Caregivers in the Digital Age: The Influence of Digital Literacy on Tele Health-Based Parent-Mediated Interventions for Children with Autism - Rabya Sammam (Research Journal of Psychology, 2025)
Parent training programs may enhance the social behaviour and communication skills of children with autism spectrum disorder (ASD), especially for families dealing with them as caregivers. Unfortunately, these activities have not been assessed. This study sought to consolidate available data from research on parent-mediated intervention training for families with children diagnosed with autism spectrum disorder (ASD) and to assess the efficiency of such home interventions based on the results. In accordance with the PRISMA declaration, a search of the following electronic databases (ERIC, PsycINFO, PubMed, Google Scholar) for studies examining parent-mediated intervention training for families with a child diagnosed with autism spectrum disorder (ASD) was performed. The results revealed that eleven studies satisfied the qualifying requirements. Remote parent-mediated intervention training may improve parents' understanding, intervention fidelity, and children's social behaviour and communication abilities. Future study should include standardised outcome measures to reduce bias, as well as evaluations of the therapy's applicability and practicality.